POLYETHYLENE FILMS FOR LONG-TERM STORAGE OF METAL PRODUCTS: REQUIREMENTS, NEEDS, PROPERTIES - DOMANTSEVYCH, NINA; YATSYSHYN, BOGDAN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The main criteria put forward to polymer coatings as means of anti-corrosion protection of metal products have considered by studies. The basic requirements of consumers for anti-corrosion protection of metal products using film materials have been established. It is shown that the use of film polymer materials for long-term protection of metal products is characterized by features due to the combination of preserving the functionality of polymer materials - protective and barrier characteristics and the preservation of the metal product itself.It was determined that the main directions in the development of film polymer coatings for long-term protection are the study of their aging processes, changes in properties depending on the terms and conditions of operation, consideration of the influence of the constituent components of the coatings on the duration of operation and the possibility of their further use. The change in the properties of polymer composites is the result of the action of many factors that can cause a positive or negative effect.The separate directions of development of works on aging of polymers, which are actively carried out today are researching on films with volatile atmospheric corrosion inhibitors of metals, plasticizers and other technological additives. At the same time, the main accent is placed on the correct selection of ingredients of coating and express analysis, despite the use of accelerated experiments, the development of appropriate mathematical apparatus for interpreting the results, improvement of research equipment.The analysis of scientific studies of the aging processes of polyethylene films during operation and the determination of the necessary directions of research will facilitate and improve the preservation of the properties of polymer materials, and extend the service life of metal products.
Keywords: polymers; polyethylene films; filler; structure; aging; closed storage